Penerapan Model Make A Match dalam Meningkatkan Kerjasama Tim pada Pembelajaran Pendidikan Agama Islam (PAI) - Yeti Hikmawati; H Sukidi; Sumiyati; Ana Shawamah; Siti Zulaicha; Syaiful Bahri (JURNAL ILMIAH RESEARCH STUDENT, 2025)
. Team collaboration in the learning process is crucial for students' character development. One teaching model that fosters teamwork is the Make A Match model. This research aims to describe the steps, advantages, and disadvantages of applying the Make A Match learning model in Islamic Education (PAI) classes at Madrasah Aliyah Negeri 1 Kebumen dan Madrasah Tsanawiyah Negeri 5 Kabupaten Karanganyar. This study uses a qualitative approach, with the research subjects being teachers at Madrasah Aliyah Negeri 1 Kebumen dan Madrasah Tsanawiyah Negeri 5 Kabupaten Karanganyar. The informants are PAI teachers. Data collection techniques include interviews, observations, and documentation. The results of this study are as follows: 1) The steps of the Make A Match model include stating the objectives, organizing students into learning teams, assisting team work, and providing rewards; 2) The advantages of the Make A Match model are that it creates an active and enjoyable atmosphere, presents engaging material, influences learning outcomes, and fosters teamwork among students; 3) The disadvantages include the need for strong teacher guidance, the need for time management, the necessity for preparation of materials and equipment, and potential classroom noise that could disrupt other classes. The conclusion of this study is that the Make A Match model can be effectively implemented in the learning process as an effort to enhance team collaboration and improve PAI learning outcomes at the Madrasah or School.